A prediction model of wellbore temperature and pressure distribution in hydrocarbon gas injection well. Issue 1 (June 2021) - Wang, Yichen; Ye, Jigen; Wu, Shuhong
Abstract: For the sake of solving the problem that it is difficult to dynamically monitor the wellbore temperature and pressure of hydrocarbon gas injection well and accurately predicting the bottom hole injection pressure, a mathematical model to describe wellbore temperature and pressure distribution is presented according to the heat transfer principle, the energy conservation law and the momentum theorem. The Shiu-Beggs wellbore temperature calculation method is used in this model to avoid errors caused by inaccurate thermodynamic parameters, and the pressure gradient equation is modified by introducing correction coefficients to improve the calculation precision of the model in practice. The fourth-order Runge-Kutta method was used to solve the model, and the new model was analyzed and verified by actual field data. The results show that the wellbore temperature is nonlinearly distributed, while the wellbore pressure is linearly distributed, and the bottom hole pressure calculated by this model is more accurate than that calculated by other methods. This study can play a certain guiding role for the injection scheme design of hydrocarbon gas injection well.